2013
DOI: 10.1016/j.bpj.2013.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Interacting Ions in Biophysics: Real is not Ideal

Abstract: Ions in water are important throughout biology, from molecules to organs. Classically, ions in water were treated as ideal noninteracting particles in a perfect gas. Excess free energy of each ion was zero. Mathematics was not available to deal consistently with flows, or interactions with other ions or boundaries. Nonclassical approaches are needed because ions in biological conditions flow and interact. The concentration gradient of one ion can drive the flow of another, even in a bulk solution. A variationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 291 publications
(324 reference statements)
1
66
0
Order By: Relevance
“…Our results suggest that this trend may be due to the progressive formation of effectively neutral ionic networks involving large numbers of strongly interacting ions. Over the longer term, our results may also prove useful for deciphering how electrostatic interactions maintain such a dominant role near the active sites of proteins, ion channels, and similar self-assembling biological systems (2), where local effective salt concentrations can exceed 10 M. samples were dried under vacuum at 373 K for at least 72 h. After drying, a droplet of RTIL (50-100 μL) was immediately injected between mica surfaces in a gas-tight SFA under dry nitrogen purge conditions, and the SFA was resealed. All experiments were performed in the presence of a reservoir of the desiccant phosphorous pentoxide (P 2 O 5 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our results suggest that this trend may be due to the progressive formation of effectively neutral ionic networks involving large numbers of strongly interacting ions. Over the longer term, our results may also prove useful for deciphering how electrostatic interactions maintain such a dominant role near the active sites of proteins, ion channels, and similar self-assembling biological systems (2), where local effective salt concentrations can exceed 10 M. samples were dried under vacuum at 373 K for at least 72 h. After drying, a droplet of RTIL (50-100 μL) was immediately injected between mica surfaces in a gas-tight SFA under dry nitrogen purge conditions, and the SFA was resealed. All experiments were performed in the presence of a reservoir of the desiccant phosphorous pentoxide (P 2 O 5 ).…”
Section: Discussionmentioning
confidence: 91%
“…As a result, the development of a general conceptual picture of concentrated electrolyte solutions remains challenging. Nevertheless, electrolytes with high ionic concentrations are prevalent in biological systems (2) and technological applications, such as energy storage devices (3)(4)(5), so overcoming this challenge remains an important task.…”
mentioning
confidence: 99%
“…Thus a single model with almost unchanging parameters can account for the valence selectivity features of both sodium and calcium channels (reviewed in Refs. [38,39]). An analytic treatment of such a model [35,40,41] showed that transport of Ca 2+ ions through a negatively doped channel exhibited several ionexchange phase transitions as functions of bulk concentration and Q f , with a near-zero transport barrier at the transition points [41].…”
Section: Introductionmentioning
confidence: 94%
“…However, numerous studies have established that accounting for finite ion size is essential in order to accurately simulate electrical double layers for large electric potentials and/or large electrolyte concentrations typical of EDLCs. [93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] Among the models accounting for the finite size of ions, the modified Poisson-Boltzmann (MPB) models are based on the local-density and mean-field approximations and are relatively convenient both mathematically and numerically.…”
Section: Equilibrium Modelingmentioning
confidence: 99%